Men as The Victim of Patriarchal System in Ocean Vuong's "On Earth We're Briefly Gorgeous" (2018) - Olivia Olivia; Delvi Wahyuni (English Language and Literature, 2022)
The aim of this research is to find out patriarchal expectation of men which leads men as the victim of patriarchal system contained in the novel “On Earth We’re Briefly Gorgeous” (2018) by Ocean Vuong. Descriptive research is used in this research to describe in detail about phenomenon or issue. The analysis has been done using Feminist Literary Theory. The result of this research is men can be victimized in patriarchal system, which is known as a system that benefits men, because some men cannot fulfil the standards of patriarchal system. The standards of patriarchal system are men must be masculine, physically and mentally, and must be heterosexual.